The Impact of Internal Marketing Dimensions on the Level of Service Quality in Libyan Commercial Banks Operating in the Municipality of Al-Beyda (Al-Mukhtar Journal of Economic Sciences, 2021)
This study aimed to identify the impact of internal marketing dimensions on the level of service quality in Libyan commercial banks operating within the administrative boundaries of the municipality of Al Beyda. The study population and sample consisted of employees in the banks under study: (7) banks, namely (Commercial Bank, Al Wahda Bank, Jumhouria Bank, Sahara Bank, Trade and Development Bank, Al-Aman Bank, North African Bank). The sample consisted of managers, their assistants and heads of departments. For the study's goal, a questionnaire was designed and distributed to the study sample, and using a simple random sample with the help of one of the sampling sites, (50) questionnaires were distributed to the target audience, and (42) were retrieved from them, (6) questionnaires were excluded due to their unsuitability for analysis, As for the number of acceptable and valid questionnaires for research, it reached (36) with a response rate of 72% of the total number of questionnaires, which is a good percentage for the scientific study. The study used Statistical Package for Social Sciences (SPSS) program to process the collected data, using descriptive and inferential statistics to analyze the data. The study reached several results, the most important of which is; There is a statistically significant effect at a level of significance less than (α = 0.05) for the areas of internal marketing (staff selection, training, motivation, internal communication and empowerment) on the level of service quality in Libyan commercial banks, in addition, the study showed no difference between the opinions of a sample The study on the impact of internal marketing on the level of service quality in the banks under investigation. Based on the study's findings, it is recommended that the banks under study adopt the concept of internal marketing by designing strategies directed to the needs and desires of their customers because of its impact on the quality of banking service.
Keywords: Internal Marketing; Internal Marketing Dimensions; Service Quality Level; Commercial Banks